2023
DOI: 10.1021/acs.analchem.2c04362
|View full text |Cite
|
Sign up to set email alerts
|

Logistic Regression Analysis of LC-MS/MS Data of Monomers Eluted from Aged Dental Composites: A Supervised Machine-Learning Approach

Abstract: Compound identification by database searching that matches experimental with library mass spectra is commonly used in mass spectrometric (MS) data analysis. Vendor software often outputs scores that represent the quality of each spectral match for the identified compounds. However, software-generated identification results can differ drastically depending on the initial search parameters. Machine learning is applied here to provide a statistical evaluation of software-generated compound identification results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…When the default classification threshold is applied (i.e., P A > 0.5 is automatically classified as emitter A), a minimum classification accuracy of 86.4% is observed, corresponding to a high true positive rate (TPR) of 0.86 and modest false positive rate (FPR) of 0.13. However, prior studies have shown that the classification threshold can be increased to maximize model accuracy 14 , 60 , 61 . Figure 2D demonstrates this principle for 5ROX versus R6G.…”
Section: Resultsmentioning
confidence: 99%
“…When the default classification threshold is applied (i.e., P A > 0.5 is automatically classified as emitter A), a minimum classification accuracy of 86.4% is observed, corresponding to a high true positive rate (TPR) of 0.86 and modest false positive rate (FPR) of 0.13. However, prior studies have shown that the classification threshold can be increased to maximize model accuracy 14 , 60 , 61 . Figure 2D demonstrates this principle for 5ROX versus R6G.…”
Section: Resultsmentioning
confidence: 99%
“…Constraints on ML models are not specific to instrument, sample type, or data analysis software (Chen et al 2023). In this study, the observed limitations associated with the quality of the models and data resulted in the need for adjustments for a better model performance.…”
Section: Discussionmentioning
confidence: 97%
“…68−70 Highlighting the power of single-molecule approaches in dynamic studies, our work contributes two new methodologies: single-molecule fluorescence anisotropy (smFA) and the single-molecule neighboring density (smND) assay. 15,16 smFA brings a new dimension to SRM by enabling the observation of intracellular viscosity through the measurement of rotational mobility of fluorescent proteins. On the other hand, the smND assay quantifies protein oligomeric states directly within cells by analyzing the spatial distribution and density of individual protein molecules.…”
Section: Enhancing Srm Through Single-molecule Approachesmentioning
confidence: 99%